Investigating the antimicrobial activity of silver nanoparticles with varying charges green-synthesized from Tabebuia rosea flower - Trung Dien Nguyen; Thao Phuc-Nguyen Nguyen; Nhung Thi-Tuyet Thai; Yen Hai Hoang; Gia Thi-Ngoc Trinh (Communications in Science and Technology, 2024)
The integration of nanotechnology and biomedicine has driven a significant interest in silver nanoparticles due to their unique properties. This study presents a novel approach by combining Tabebuia rosea flower extract and chitosan to manipulate the surface charges of synthesized silver nanoparticles. These biosynthesized nanoparticles, presenting negative, neutral, and positive charges, were thoroughly analyzed by means of a number of techniques including Ultraviolet-visible spectroscopy, X-ray diffraction, transmission electron microscopy, and Fourier-transform infrared spectroscopy. By incorporating chitosan, the zeta potential of the green-synthesized nanomaterials was modified, shifting from negative to positive. The resultant silver nanoparticles showed the zeta potentials of –24.8 mV for negatively charged particles, +22.9 mV for positively charged ones, and neutrality at approximately 0.04% chitosan. Meanwhile, the particle sizes for the negative, neutral, and positive nanomaterials were 19.7, 15.8, and 14.2 nm, respectively. The antimicrobial and anticancer activities of these biosynthesized nanoparticles were evaluated against gram-negative bacteria (Pseudomonas aeruginosa, Escherichia coli, and Salmonella enterica), gram-positive bacteria (Bacillus subtilis, Lactobacillus fermentum, and Staphylococcus aureus), and cancer cell lines (A549, Hep-G2, KB, and MCF-7). These results highlight the crucial role of surface stabilizers, particle size, and charge in determining the biomedical potential of nanosilver particles. Notably, the biosynthesized silver nanoparticles exhibited a number of promising antimicrobial and anticancer properties, emphasizing their potential for biomedical applications.